The role of post-pyrolysis carbon dioxide capture in hydrogen recovery from waste-derived pyrolysis gas - Wang, Yuxin (2024)
The study elucidated the role of post-pyrolysis CO2 removal using a CaO sorbent on upgrading pyrolysis gas into H2-rich gas. The pyrolysis gas was obtained from various waste-derived feedstocks (municipal sewage sludge, refused derived fuel (RDF), pine sawdust (biomass), and marine litter) by pyrolysis (600 °C), and underwent the treatment with CaO (600 °C) followed by the thermolytic decomposition at 1300 °C. The results show that CaO utilization does not change significantly H2 yield and higher heating value of gas on a feedstock mass basis but increases H2 purity from 49.6–83.3 to 63.7–94.4 vol% and H2/CO ratio from 1.1–5.7 to 1.9–19.8 of the product gas across all feedstocks. Normalized rate constants K for CO2 capture by CaO, determined by the grain model, varied between 0.0001 and 0.0006 min−1, revealing the feedstock-specific effectiveness of CaO. The higher CaO consumption rates were observed in case of RDF and biomass compared to sludge and marine litter. This could be attributed to the coking and faster carbonation of CaO caused by the composition of pyrolytic products. The obtained results emphasize the potential of integrating CaO sorbent into pyrolysis-based processes for the production of decarbonized H2-rich gas with higher purity. Moreover, the use of normalized kinetic parameters provides a straightforward method for the selection of feedstocks suitable for decarbonization of pyrolysis gas using CaO sorbent. The predominant factor affecting the carbonation kinetics of the CaO sorbent was found to be the CO2 flow rates in their respective pyrolysis gases.